Bile bilirubin pigment analysis in disorders of bilirubin metabolism in early infancy - Lee, Way Seah; McKiernan, P.J.; Beath, S.V.; Preece, M.A.; Baty, D.; Kelly, D.A.; Burchell, B.; Clarke, D.J. (BMJ Publishing Group, 2001)
BACKGROUND Early and accurate diagnosis of CriglerâNajjar syndrome, which causes prolonged unconjugated hyperbilirubinaemia in infancy, is important, as orthotopic liver transplantation is the definitive treatment. AIM To determine whether bilirubin pigment analysis of bile in infants with prolonged unconjugated hyperbilirubinaemia provides useful diagnostic information in the first 3 months of life. METHODS Retrospective review of patients with prolonged unconjugated hyperbilirubinaemia referred to the liver unit, Birmingham Children's Hospital, for the diagnosis of CriglerâNajjar syndrome. Bile bilirubin pigment composition was determined by high performance liquid chromatography. Initial diagnoses were made based on the result of bile bilirubin pigment composition. Final diagnoses were made after reviewing the clinical course, response to phenobarbitone, repeat bile bilirubin pigment composition analysis, and genetic studies. RESULTS Between 1992 and 1999, nine infants aged less than 3 months of age with prolonged hyperbilirubinaemia underwent bile bilirubin pigment analyses. Based on these, two children were diagnosed with CriglerâNajjar syndrome (CNS) type 1, six with CNS type 2, and one with Gilbert's syndrome. Five children whose initial diagnosis was CNS type 2 had resolution of jaundice and normalisation of serum bilirubin after discontinuing phenobarbitone, and these cases were thought to be normal or to have Gilbert's syndrome. One of the initial cases of CNS type 1 responded to phenobarbitone with an 80 reduction in serum bilirubin consistent with CNS type 2. In all, the diagnoses of six cases needed to be reviewed. CONCLUSIONS Early bile pigment analysis, performed during the first 3 months of life, often shows high levels of unconjugated bilirubin or bilirubin monoconjugates, leading to the incorrect diagnosis of both type 1 and type 2 CriglerâNajjar syndrome.